The unexpected weakness: A case report of spontaneous spinal epidural hematoma (Indian Journal of Case Reports, 2020)
Spontaneous spinal epidural hematoma is an uncommon cause of acute spinal cord compression. It is a neurologic emergency; urgent imaging and surgical intervention prevent permanent neurologic sequelae. Here, we present the case of a 71-year-old female known to have diabetes mellitus, hypertension, and ischemic heart disease on treatment. She presented to the emergency department with sudden onset of upper back pain with chest discomfort and bilateral lower limb weakness with numbness, which was waxing and waning for 4–6 h. On examination, there were no pulse or blood pressure deficits bilaterally and neurologically power that was 3/5 in both lower limbs with decreased tone and reflexes. In view of possible myeloradiculopathy, a magnetic resonance imaging whole spine was done which showed a lesion in the posterior epidural space, suggestive of hematoma, causing compression of the posterior thecal sac. The final diagnosis was spontaneous C7-T2 epidural hematoma secondary to antiplatelet therapy.